Integrasi Termometer dalam Otomatisasi Hand Sanitizer Berbasis Arduino Uno - yogi priyo istiyono; Murdiono Murdiono (Emitor: Jurnal Teknik Elektro, 2023)
Every day-to-day activity the hands are often contaminated with viruses, so the hands intermediary the entry of viruses into the body that cause a disease.  One of the efforts to prevent or reduce the spread of the Covid-19 Virus is to wash their hands more diligently, but it is not uncommon for someone to ignore it by washing their hands.  So an automatic Hand Sanitizer tool was designed which is equipped with an automatic body temperature check, using the LM35 temperature sensor as a body temperature detector, a DC Servo Motor drive as a pressure giver to the Hand Sanitizer, as well as using a Solenoid door lock to lock the door and Arduino UNO as the microcontroller for its control with the display on this LCD aims to reduce the spread of the Covid-19 Virus by checking human body temperature and  washing hands with Hand Sanitizer automatically and creating an integrated system of automatic doors, washing hands, and automatic doors to prevent the spread of the corona virus by checking body temperature using an LM35 sensor.  If a person's body temperature is below 37 oC then the Hand Sanitizer will automatically release liquid, then the door lock solenoid door lock will activate and the door lock will open.